Articuler protection des ressources en eau et accès à l’eau potable en Indonésie : quel cadre d’analyse ? - Catherine Baron; Héloïse Valette (Développement Durable et Territoires)
This article is based on the observation that issues relating to drinking water access are often disconnected from those relating to water resource governance, both in academic circles (particularly in economics and management) and within institutions (ministries, donors, NGOs). The aim of this paper is to analyse the relationship between these issues, based on the interpretation of a "conflict of disconnection" in Indonesia. This conflict reflects both a disconnection between representations and perceptions of water(s) that are not shared by actors (water as a resource, a public good, commodity, right, common, etc.), and a disconnection between resource and service from the point of view of governance and coordination rules. Based on this conflict, a framework for analyzing articulation is proposed based on four components : modes of coordination between actors, rules of coordination, scales and socio-technical devices. The identification of a plurality of qualifications and classifications of water, alongside underlying actors' representations and strategies, makes it possible to identify power relationships within a territory. This cross-cutting approach is seen as structuring our analysis. The article provides an original perspective for identifying the conditions of change for water governance that integrates sustainability issues in the global South.